Biohydrogen Production Through Dark Fermentation. Issue 4 (7th February 2020) - Sarangi, Prakash K.; Nanda, Sonil
Abstract: Waste organic biomass is regarded as the most suitable renewable source for conversion to produce biofuels and biochemicals. Owing to its high‐energy potential and abundancy, lignocellulosic biomass can be utilized to produce alternative energy in the form of gaseous and liquid biofuels. Microbial conversion of waste biomass is the most successful technology for the generation of biohydrogen through dark fermentation. Different biological hydrogen production technologies along with process parameters are described in this review paper with the focus on dark fermentation. The production of biohydrogen from various substrates is summarized along with the integrated mode of dark fermentation and photofermentation. Hydrogen generation through biological water‐gas shift reaction is also highlighted. Abstract : Hydrogen is an excellent energy vector and carrier. Dark fermentation as well as integrated dark fermentation and photofermentation are environmentally benign routes for biological hydrogen production. Optimization of fermentation parameters as well as employing versatile microorganisms can result in maximizing biohydrogen production from a wide variety of organic residues.